Association between air pollution exposure and exhaled nitric oxide in an elderly population - Adamkiewicz, G; Ebelt, S; Syring, M; Slater, J; Speizer, F E; Schwartz, J; Suh, H; Gold, D R (Thorax, 2004)
Background: Animal models suggest that the cardiovascular effects of air pollution result in part from inflammation caused by proinflammatory mediators originating in the lung. In a human study of the cardiovascular effects of air pollution, we aimed to evaluate the potential association between air pollution levels and the fraction of exhaled nitric oxide (FeNO), a non-invasive measure of airway inflammation. Methods: Breath samples were collected weekly between September and December 2000 in a community based group of elderly subjects (median age 70.7 years) in Steubenville, Ohio. The samples were analysed for NO. Air pollution levels were measured concurrently at a central site monitor. Results: An increase in the 24 hour average PM2.5 concentration of 17.7 µg/m3 was associated with an increase in FeNO of 1.45 ppb (95% CI 0.33 to 2.57) in models adjusted for subject, week of study, day of the week, hour of the day, ambient barometric pressure, temperature, and relative humidity. This represents a change of approximately 15% compared with the mean FeNO in the cohort (9.9 ppb). A significant association was also observed for a 24 hour moving average of ambient NO (0.83 ppb increase, 95% CI 0.26 to 1.40). In two-pollutant models, the magnitude and precision of the PM2.5 effect was not reduced and the ambient NO effect was no longer significant. The associations between FeNO and PM2.5 were significantly higher in subjects with a doctor’s diagnosis of COPD (p value for interaction = 0.03). Conclusions: Ambient pollution may lead to airway inflammation as measured by FeNO. These subclinical inflammatory changes may be an important step in the pathogenesis of the cardiopulmonary effects induced by exposure to air pollution.